2013
DOI: 10.1099/vir.0.048637-0
|View full text |Cite
|
Sign up to set email alerts
|

Piscine reovirus encodes a cytotoxic, non-fusogenic, integral membrane protein and previously unrecognized virion outer-capsid proteins

Abstract: Piscine reovirus (PRV) is a tentative new member of the family Reoviridae and has been linked to heart and skeletal muscle inflammation in farmed Atlantic salmon (Salmo salar L.). Recent sequence-based evidence suggests that PRV is about equally related to members of the genera Orthoreovirus and Aquareovirus. Sequence similarities have also suggested that PRV might encode a fusion-associated small transmembrane (FAST) protein, which in turn suggests that PRV might be the prototype of a new genus with syncytium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 51 publications
9
67
0
Order By: Relevance
“…PRV-2 encodes homologues of all the genes that are found in PRV (λ1, λ2, λ3, μ1, μ2, μNS, σ1, σ2, σ3, σNS, and p13). Previous studies have suggested that the presence of an integral membrane protein, p13, and two essential outer capsid proteins, σ3 and σ1, has important implications for the unique evolution and taxonomic classification of PRV [22, 26, 27]. In PRV, the p13 membrane protein is encoded on the same segment as the σ3 protein, in a bicistronic segment, whereas the σ1 protein is encoded on a monocistronic segment, rather than on a bi- or tricistronic segment [22, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…PRV-2 encodes homologues of all the genes that are found in PRV (λ1, λ2, λ3, μ1, μ2, μNS, σ1, σ2, σ3, σNS, and p13). Previous studies have suggested that the presence of an integral membrane protein, p13, and two essential outer capsid proteins, σ3 and σ1, has important implications for the unique evolution and taxonomic classification of PRV [22, 26, 27]. In PRV, the p13 membrane protein is encoded on the same segment as the σ3 protein, in a bicistronic segment, whereas the σ1 protein is encoded on a monocistronic segment, rather than on a bi- or tricistronic segment [22, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…GCRV-HZ08/GD108 and GCRV104 possess the 11-segment profile of approved Aquareovirus members, whereas PRV has the 10-segment profile of approved Orthoreovirus members. We have recently reported that PRV is also like some orthoreoviruses, and unlike approved aquareoviruses, in encoding an outer-fiber protein, p35, and also in not encoding an NS-FAST protein [32] (Tables 1, 2, and S1). The additional NS protein encoded by PRV, p13, is instead a cytotoxic integral-membrane protein that localizes to cytosolic compartments, not to the plasma membrane as do FAST proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Scophthalmus maximus reovirus, a novel reovirus isolated from marine fish, contains a FAST protein translated from a non-AUG start site that has been shown to partially contribute to the cytopathic effect caused by infection with this virus [94]. As a new reovirus equally related to members of the Orthoreovirus and Aquareovirus genera, Piscine reovirus, which is linked to heart and skeletal muscle inflammation in farmed Atlantic salmon (Salmo salar L.), has been suggested by whole genome comparisons to be more closely related to orthoreoviruses and, therefore, a new species of the Orthoreovirus genus [96]. Genome comparisons show that Piscine reovirus contains 10 genomic segments (not 11 as in all recognized aquareoviruses) and an outer-fiber protein that is present in most members of the Orthoreovirus genus [96,97].…”
Section: Aquareovirus Genomesmentioning
confidence: 99%
“…As a new reovirus equally related to members of the Orthoreovirus and Aquareovirus genera, Piscine reovirus, which is linked to heart and skeletal muscle inflammation in farmed Atlantic salmon (Salmo salar L.), has been suggested by whole genome comparisons to be more closely related to orthoreoviruses and, therefore, a new species of the Orthoreovirus genus [96]. Genome comparisons show that Piscine reovirus contains 10 genomic segments (not 11 as in all recognized aquareoviruses) and an outer-fiber protein that is present in most members of the Orthoreovirus genus [96,97]. Moreover, phylogenetic evidence of long distance dispersal and transmission has been revealed by comparing the protein coding sequences S1, S2 and S4 in Piscine reovirus genomic segments between farmed and wild Atlantic salmon [98].…”
Section: Aquareovirus Genomesmentioning
confidence: 99%